STATUS DAN KEDUDUKAN LEMBAGA PERKREDITAN DESA (LPD) TERKAIT PENGIKATAN JAMINAN DENGAN BERLAKUNYA UNDANG-UNDANG NOMOR 1 TAHUN 2013 TENTANG LEMBAGA KEUANGAN MIKRO - Devi Jayanthi, Ni Made; Wairocana, I Gust i Ngurah; Wiryawan, I Wayan (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 2 (2017)DO - 10.24843/AC.2017.v02.i02.p04, 2017)
Lembaga Perkredi tan Desa (LPD) i s a f inancial inst i tut ion owned by desa pakraman which has special characteri st ics. The said special charac teri st ic, speci f ical ly located on the obl igat ions of LPD to desa pakraman which has a physical nature/ sekala and al so a non -physical nature/ni skala. These caused our cent ral government to grant exclusion on the exi stence of LPD i t sel f in Law No. 1 Year 2013 regarding Micro Financial Inst i tut ion. The type of thi s research i s an appl ied normat ive legal research by t racing document s as primary legal material s. Thi s research used statue and conceptual approaches. LPD i s only exi st in Bal i , therefore, LPD i s o nly become a legal subject to Adat Law in Bal i . The said exclusion has rai sed a confusion since al l thi s t ime the legal status and standing of LPD in every regulat ion i s considered equal to a regular Financial Inst i tut ion. Therefore, in order to legal ly bi nd a guarantee in a credi t t ransact ion i t must always refer to the legi slat ion in accordance wi th our posi t ive law.